EFFECT OF VERMICOMPOST AND BIOFERTILIZATION ON THE AVAILABILITY OF SOME SOIL NUTRIENTS, GROWTH AND YIELD OF SQUASH (Cucurbita pepo L.) - Waldan.A.A. Ibrahim,; H. A. Abdul- Ratha, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was carried out to evaluate the effect of  four application methods of vermicompost tea (without application, ground application, foliar spray, combination of - ground application + foliar spray) , four types of biofertilization (without application, Stenotrophomonas maltophilia, Bacillus megaterium, the combination consisting of S. maltophilia + B. megagaterium), and two levels (0, 50%) of the fertilizer recommendation in the availability of some soil nutrients and on the growth and yield of squash using as randomized complete block design with three replications. The results showed that the triple interaction of the combination of application  vermicompost tea with the combination of biofertilizer and 50% of mineral fertilizer was effect significantly and gave the highest values for some vegetative growth parameters. Which included the dry weight of the vegetative part, the length and weight of the root, and total yield which amounted 196.35 g plant-1, 65.33 cm, 60.31 g plant-1, 45.14 Mgha-1, respectively. the  available of nitrogen, phosphorous and potassium in soil at the end of the experiment, which amounted 60.56, 38.20 and 191.38 mg kg-1soil in comparison with the treatment without addition, which gave the lowest rates.